2004
DOI: 10.1097/01.asn.0000105993.63023.d8
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Estrogens on Indices of Renal Damage in Uninephrectomized SHRsp Rats

Abstract: Abstract. Renal diseases tend to be less severe among premenopausal female patients, compared with male patients. Experimental data on the effects of estrogens on renal damage are controversial, and potential underlying mechanisms have not been fully clarified. Three-month-old, female, uninephrectomized (UNX), sham-operated or ovariectomized (OVX) SHRsp rats were left untreated or received either 17␤-estradiol 3-benzoate (25 g/d) or estriol (0.02 mg/d) daily. After 3 mo, indices of renal damage (glomeruloscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 49 publications
5
64
0
Order By: Relevance
“…50 The estrogen-like antifibrotic effects are possibly related to the reduction in TGF-b expression. [43][44][45]49,50,53,54 It is interesting to note that these reported renoprotective effects of estrogens parallel the findings observed for tamoxifen in this study. 47 All effects of estrogens are mediated via ER, intracellular transcription factors that regulate the transcription of target genes.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…50 The estrogen-like antifibrotic effects are possibly related to the reduction in TGF-b expression. [43][44][45]49,50,53,54 It is interesting to note that these reported renoprotective effects of estrogens parallel the findings observed for tamoxifen in this study. 47 All effects of estrogens are mediated via ER, intracellular transcription factors that regulate the transcription of target genes.…”
Section: Discussionsupporting
confidence: 76%
“…However, modifications of sex hormone status, such as estrogen deficiency induced by ovariectomy, are shown to worsen renal damage and accelerate the progression of renal disease in several models of kidney disease. [42][43][44][45][46] Studies using 17b-estradiol, 2-hydroxyestradiol, or estriol replacement provide evidence that estrogen or estrogen metabolites have a beneficial effect ameliorating renal damage. [43][44][45][46][47][48] For example, the data showed that estrogen or estrogen metabolites reduced albuminuria, attenuated renal lesions, and prevented disease progression in a wide variety of experimental models of renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time course analysis of podocyte injury revealed that desmin, an early injury marker, 28 was already expressed in some glomeruli of DSHs at 2 weeks of salt loading ( Figure 3A and 3B). We further assessed podocyte damage by transmission electron microscopy ( Figure 3C).…”
Section: Podocyte Injury Commences At Early Stage In Dshmentioning
confidence: 99%
“…28 Glomerular B7-1 staining was semiquantitated as the percentage of B7-1-positive glomeruli per total glomeruli counted. Nephrin staining was scored into 0, 0.5ϩ, and 1ϩ, according to the scoring system reported previously with some modification.…”
Section: Immunohistochemistrymentioning
confidence: 99%